Prevalence of hypogonadism in male patients with renal failure. Issue 972 (26th October 2006) - Albaaj, F; Sivalingham, M; Haynes, P; McKinnon, G; Foley, R N; Waldek, S; O'Donoghue, D J; Kalra, P A
Abstract : Background: Hypogonadism in men may be secondary to renal failure and is well recognised in patients with end-stage renal disease. It is thought to contribute to the sexual dysfunction and osteoporosis experienced by these patients. However, the association between hypogonadism and lesser degrees of renal dysfunction is not well characterised. Methods: The gonadal status of 214 male patients (mean age 56 (SD 18) years) attending a renal centre was studied; 62 of them were receiving haemodialysis and 22 continuous ambulatory peritoneal dialysis for end-stage renal disease, whereas 34 patients had functioning renal transplants and 96 patients were in the low-clearance phase. Non-fasting plasma was analysed for testosterone, follicle-stimulating hormone, luteinising hormone, sex hormone-binding globulin, parathyroid hormone and haemoglobin. Creatinine clearance was estimated in patients not on dialysis, and Kt/V and urea reduction ratio were assessed in patients on dialysis. Testosterone concentrations were classified as normal (>14 nmol/l), low-normal (10–14 nmol/l) or low (<10 nmol/l). Results: 56 (26.2%) patients had significantly low testosterone levels and another 65 (30.3%) had low-normal levels. No significant changes were seen in sex hormone-binding globulin or gonadotrophin levels. Gonadal status was not correlated with haemoglobin level, parathyroid hormone level, creatinine clearance, or dialysis duration or adequacy. Conclusion: Over half of patients with renal failure, even in the pre-dialysis phase, have low or low-normal levels of testosterone, which may be a potentially reversible risk factor for osteoporosis and sexual dysfunction. These patients may be candidates for testosterone-replacement therapy, which has been shown to improve bone mineral-density and libido in men with low and low-normal testosterone levels.